# Demonstrate using determinant properties that the determinant of $A$ is equal to $2abc(a+b+c)^3$

How can I show using properties of determinants that:

$$\det\begin{pmatrix} (b+c)^2 & a^2 & a^2 \\ b^2 & (c+a)^2 & b^2 \\ c^2 & c^2 & (a+b)^2 \\ \end{pmatrix} = 2abc(a+b+c)^3$$

• Starting with Sarrus en.wikipedia.org/wiki/Rule_of_Sarrus ?? – MattAllegro Oct 1 '14 at 22:35
• Sorry i already know the Sarrus law. The matter is to get the result using the properties of determinants like: $det(B)=-det(A)$ if $B$ is $A$ with two columns interchanged. Or $det(B)=Kdet(A)$ IF $B$ is $A$ with a column multiplied by $K$, there are some few known importants properties of determinantes of linear algebra. It is no requested to use some weird properties. – JuanMuñoz Oct 1 '14 at 22:50
• @Amzoti I have already use Sarrus Law, but it get to much complicated, in this excersise is just requested to avoid using that law, and get the result in a simpler way using de correct properties of determinants. – JuanMuñoz Oct 1 '14 at 22:59
• @MattAllegro I just wrote you something after your comment but I forgot to call you, maybe the next comment I did, could help you to indicate a better way to proceed. – JuanMuñoz Oct 1 '14 at 23:03
• See also How to solve this determinant. Found using Approach0 – Martin Sleziak Jan 10 '17 at 5:52

it is easy to see that it vanishes if $a=0$, $b=0$ or $c=0$.
and if $a+b+c=0$ then $(b+c)^2=a^2$ etc. , so again the determinant vanishes.
hence for suitably chosen $\lambda$ and $\mu$ $$D(a,b,c) = abc(a+b+c)\left(\lambda (a^2+b^2+c^2) + \mu(ab+bc+ca) \right)$$ we may easily compute $D(1,1,1)=54$, hence $$\lambda+\mu = 6$$ likewise $D(2,1,1) = 256$, giving: $$6\lambda +5 \mu = 32$$thus $\lambda=2$ and $\mu=4$, so $$\lambda (a^2+b^2+c^2) + \mu(ab+bc+ca) = 2(a+b+c)^2$$ and, finally: $$D(a,b,c) = 2abc(a+b+c)^3$$
• This needs solved like this $$\det\begin{pmatrix}1 & 1 & 1 \\ x & y & z \\ x^2 & y^2 & z^2 \\ \end{pmatrix} = \det\begin{pmatrix}1 & 0 & 0 \\ x & y-x & z-x \\ x^2 & y^2-x^2 & z^2-x^2 \\ \end{pmatrix} = \det\begin{pmatrix}y-x & z-x \\ y^2-x^2 & z^2-x^2 \\ \end{pmatrix} = \det\begin{pmatrix}y-x & z-x \\ (y-x)(y+x) & (z-x)(z+x) \\ \end{pmatrix}=(y-x)(z-x)\det\begin{pmatrix} 1 & 1 \\ y+x & z+x \\ \end{pmatrix} = (y-x)(z-x)\det\begin{pmatrix} 1 & 0 \\ y+x & z-y \\ \end{pmatrix}=(y-x)(z-x)(z-y)$$ – JuanMuñoz Oct 3 '14 at 21:58
• How can you write $D(a,b,c) = abc(a+b+c)\left[\lambda (a^2+b^2+c^2) + \mu(ab+bc+ca) \right]$ after you obtained $abc(a+b+c)$ as factor ? – ss1729 Feb 28 '18 at 7:56
• that is the form is must take if it is a homogeneous symmetric polynomial of degree six divisible by $abc(a+b+c)$. – David Holden Feb 28 '18 at 12:03